Юзовка – Сталино – Донецк: политизация национального вопроса в прозе о Донбассе советских писателей 1930–1980-х гг. - Shestakova, Eleonora (Studia Rossica Posnaniensia, 2024)
Donetsk is a young industrial city. This is captured in the history of its naming, reflective of the transformations of the politics of the two empires: Yuzovka – Stalino – Donetsk. There are few fictional works devoted to Donetsk in Soviet literature. It is local, regional literature, created by natives of the region from the 1930s to the 1980s. Donetsk’s art-journalistic metatext was formed along with the city transforming itself from a worker’s settlement into the capital of industrial Donbass. After October 1917 the city and metatext of Donetsk consistently “did not remember”, “did not see” its origins – Yuzovka – but was concentrated on the Soviet present of the region. The historically conditioned multinational of Yuzovka, under the pressure of Soviet policy and ideology, was transformed into an internationality based on the dominance of the Soviet (essentially Russian) man and his local kind: the Donbasovets. The aspirations to level out the national diversity of the region, to obscure the role of people with Ukrainian roots, and to replace it with the politicised internationalization in the fabric of the works have found their semantic and ideological limit. This limit intensified when the depersonalisation of national-cultural features of the city, region was artificially imposed and it manifested in speech, everyday realities, and the memorial culture of the common people.